Entendemos el contexto de la muerte de Jesús - Flores Cherre, Armando Alfonso (2021)
In this pedagogical research he seeks to support the theoretical and pedagogical framework in this academic activity. Well, the teacher takes Sacred Scripture as a reference and what the Judeo-Christian doctrine proposes through the Catechism and its theology, in this sense this work is theoretically based on these bases. From the pedagogical level, the constructivist and socio constructivist approach is assumed with the intention that it is the student who elaborates their learning and can give reasons for their faith. So analyze the entire religious and political context in which the trial that led to the death of Jesus was experienced. It is also worth mentioning that the teacher makes use of a whole set of methodological strategies from videos, the Bible, readings with the intention that the student can develop their skills and consequently their learning acquires significance. Finally, the teacher seeks that the students are very clear that although Jesus immolated himself for our salvation, nevertheless there was a religious and political scenario that led Jesus to a death on the cross.